The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Symposium on Computational Fabrication 2020
DOI: 10.1145/3424630.3425415
|View full text |Cite
|
Sign up to set email alerts
|

RobotSculptor: Artist-Directed Robotic Sculpting of Clay

Abstract: We present an interactive design system that allows users to create sculpting styles and fabricate clay models using a standard 6-axis robot arm. Given a general mesh as input, the user iteratively selects sub-areas of the mesh through decomposition and embeds the design expression into an initial set of toolpaths by modifying key parameters that affect the visual appearance of the sculpted surface finish. These parameters were identified and extracted through a series of design experiments, using a customized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Thus, shape grammar-based design and making can inspire human-machine collaborations as it ensures both rationality and openness at the same time. Such an idea can be found in architectural experiments such as 'Interactive robotic plastering' [8], 'RobotSculptor' [12], and 'RoMA' [13]. From different scales, these projects have demonstrated the technical feasibility of interactive human-robot collaborations and the possibility of real-time bi-directional communication between humans, cyber, and physical systems.…”
Section: Shape Grammar-based Design and Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, shape grammar-based design and making can inspire human-machine collaborations as it ensures both rationality and openness at the same time. Such an idea can be found in architectural experiments such as 'Interactive robotic plastering' [8], 'RobotSculptor' [12], and 'RoMA' [13]. From different scales, these projects have demonstrated the technical feasibility of interactive human-robot collaborations and the possibility of real-time bi-directional communication between humans, cyber, and physical systems.…”
Section: Shape Grammar-based Design and Makingmentioning
confidence: 99%
“…Human-guided robotic fabrication allows humans to interact with robots in real-time and to manipulate physical form during the fabrication process. Mitterberger et al suggested such a semi-autonomous system setup features either manual handcraft with robotic precision or dynamic fabrication based on human-robot collaboration [12]. On one hand, handcrafting with robotic precision can establish a safer collaboration environment in which it requires devices to provide live feedback on design information and to help correct fabricators' operations.…”
Section: Human-guided Robotic Fabricationmentioning
confidence: 99%
“…A third example is transforming traditional tools for sculpting using clay into advanced tools for robotic sculpting. In the project RobotSculptor: Artist-Directed Robotic Sculpting of Clay at Gramazio Kohler Research, a loop tool was utilised for advanced robotic sculpting in clay (Ma et al, 2020). A style for sculpting was developed, and the sculpting process was then automated and executed using the robot's arm (Ma et al, 2020).…”
Section: Digital Ceramic Craftsmanshipmentioning
confidence: 99%
“…In the project RobotSculptor: Artist-Directed Robotic Sculpting of Clay at Gramazio Kohler Research, a loop tool was utilised for advanced robotic sculpting in clay (Ma et al, 2020). A style for sculpting was developed, and the sculpting process was then automated and executed using the robot's arm (Ma et al, 2020). However, the sculpting process was based on something other than the craftsperson's direct interaction with the material since it was automated.…”
Section: Digital Ceramic Craftsmanshipmentioning
confidence: 99%